The Urgency of Cooperative Development in Rural Areas of Indonesia - Masyhuri, Muhammad Ali (DAS Institute, 2024)
This article will discuss the importance of developing cooperatives in rural areas of Indonesia as an effort to improve the people's economy. The facts show that cooperatives can be a forum for rural communities to develop local economic potential and improve welfare. Rural areas in Indonesia have great economic potential, but are often not utilized optimally. The development of cooperatives in rural areas can be a solution to empower communities and encourage community economic growth. Various studies show that cooperatives can be an effective forum for rural communities to develop businesses, increase access to capital, and market local products. Cooperatives also play a role in encouraging innovation and technology adoption in rural areas. This article uses a qualitative approach using case study methods on several cooperatives in rural areas, showing that the development of cooperatives in rural areas can increase community income, encourage business diversification, and strengthen local economic resilience. Ultimately, the development of cooperatives in rural areas of Indonesia is a very important effort to improve the people's economy and community welfare